Implementation of the Wafa Method in Learning to Memorize the Qur'an at Integrated Islamic Junior High School - Rani, Ahmad Noor; Romelah, Romelah; Boy, Pradana (PAI RAFAH, 2024)
This study aims to determine the implementation of the Wafa method in learning to memorize the Qur'an at SMPIT Ash-Shohwah Berau East Kalimantan, to find out the advantages and disadvantages of the Wafa method in learning to memorize the Qur'an at SMPIT Ash-Shohwah Berau and to find out how to follow up on the shortcomings and advantages of the Wafa method in learning to memorize the Qur'an at SMPIT Ash-Shohwah Berau. The results showed that the implementation of Wafa media in learning the Qur'an at SMPIT Ash-Shohwah Berau is divided into three stages, namely planning, implementation, and evaluation of learning. The advantages are using strategies and languages that are easy to understand, implementation of methods that are very active and cheerful, with movements and songs, and teachers and students have a very close bond, more systematic, perfecting the memorization of the Qur'an from the aspect of tajweed, services from official institutions. Wafa is more supportive than other memorization methods. The disadvantages are learning challenges, limited learning media, lack of emphasis on understanding the meaning of the memorized Qur'an, and the number of tahfidz teachers. Efforts made to follow up on any shortcomings in the Wafa system implemented are increasing the number of repetitions of memorizing the Qur'an by adjusting the level of student intelligence, increasing teacher competence, and teachers know the content even though it is only an outline, At SMPIT Ash-Shohwah we have tried to implement collaborative learning between teachers and parents, making policies for teachers who are unable to teach to be obliged to replace at other times, and the teaching and learning process is a form of certification for Wafa students in Al-Qur'an memorization lessons for teachers of other subjects to be able to replace them. Tahfidz teachers who are unable to attend